2011
DOI: 10.1124/dmd.111.040147
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Metabolism of Chlorogenic Acids in Cultured Gastric Epithelial Monolayers

Abstract: ABSTRACT:Gastric absorption of feruloylquinic acid and di-O-caffeoylquinic acid analogs has never been investigated despite their potential contribution to the proposed beneficial health effects leading to reduced risk of type 2 diabetes. Using a cultured gastric epithelial model, with an acidic apical pH, the relative permeability coefficients (P app ) and metabolic fate of a series of chlorogenic acids (CGAs) were investigated. Mechanistic studies were performed in the apical to basal direction and demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 39 publications
7
58
0
1
Order By: Relevance
“…Despite different functions and morphology between gastric epithelial and Caco-2 cell monolayers, similar absorptive patterns were observed among both cellular lines. The absorption percentage of spent coffee CQAs was 0.3% of the apical dose, in agreement with the findings of Farrell et al (2011a). In their study, Farrell et al found that the percentage of FQAs and CQLs transported across the gastric cell monolayer was slightly higher than that of CQAs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Despite different functions and morphology between gastric epithelial and Caco-2 cell monolayers, similar absorptive patterns were observed among both cellular lines. The absorption percentage of spent coffee CQAs was 0.3% of the apical dose, in agreement with the findings of Farrell et al (2011a). In their study, Farrell et al found that the percentage of FQAs and CQLs transported across the gastric cell monolayer was slightly higher than that of CQAs.…”
Section: Discussionsupporting
confidence: 77%
“…In their study, Farrell et al found that the percentage of FQAs and CQLs transported across the gastric cell monolayer was slightly higher than that of CQAs. The only difference between gastric and intestinal cells was the percentage of diCQAs transported, due to the high permeability observed in gastric cells (Farrell et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…). Considering a possible gastric residence time from 0.2 up to 3.8 h , a CGA uptake and methylation in the stomach is conceivable . Plasma appearance is linearly correlated to the most compounds within the different ingested doses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can be inferred that ChA might target liver and induce a protective effect. Farrell et al have studied the absorption and metabolism of ChA in cultured gastric epithelial monolayers [14], but cell experiment has its intrinsic limits. Pharmacokinetics of ChA extracted from Shuang-Huang-Lian [15], Yin-Huang granules [16], Aidi lyophilizer [17], or Daqingye [18] was also studied, while little in LJF.…”
Section: Discussionmentioning
confidence: 99%